Survival trends in chemotherapy exposed metastatic bladder cancer patients and chemotherapy effect across different age, sex, and race/ethnicity - Sorce, Gabriele; Chierigo, Francesco; Flammia, Rocco Simone; Hoeh, Benedikt; Hohenhorst, Lukas; Tian, Zhe; Goyal, Jordan A; Graefen, Markus; Terrone, Carlo; Gallucci, Michele; Chun, Felix K H; Saad, Fred; et al. (Urologic oncology, 2022)
PURPOSE: To test for survival differences in metastatic urothelial carcinoma of the urinary bladder (mUCUB) patients, according to years of diagnosis, age, sex, and race/ethnicity over time and for the effect of chemotherapy on overall mortality (OM). MATERIALS AND METHODS: Within the Surveillance, Epidemiology, and End Results (2000-2016), we identified 6860 mUCUB patients. Of those, 3,249 were exposed to chemotherapy. Kaplan-Meier plots and Cox regression models focused on OM. First, we tested the effect of years of diagnosis (historical [2000-2005] vs. intermediate [2006-2011] vs. contemporary [2012-2016]) in chemotherapy exposed mUCUB patients. Second, we tested the effect of chemotherapy in all mUCUB patients. RESULTS: In chemotherapy exposed mUCUB patients according to historical vs. intermediate vs. contemporary years, median overall survival was 11 vs. 13 vs. 14 months respectively, which translated into hazard ratios (HR) of 0.86 (P = 0.005) and 0.75 (P < 0.001) in intermediate and contemporary vs. historical, respectively. Subgroup analyses in <70 years old, males and Caucasians were in agreement regarding statistically significant differences between historical vs. intermediate vs. contemporary, respectively. In multivariable Cox regression models fitted in the entire mUCUB cohort, chemotherapy exposure reduced OM (HR: 0.46; P < 0.001). Virtually the same results were recorded in age, sex, and race/ethnicity subgroups analyses. CONCLUSIONS: Contemporary chemotherapy exposed mUCUB patients exhibited better survival than their historical and intermediate counterparts. Chemotherapy reduced mortality by half, across all patient types.
Keywords: Cancer; program SEER; proporcionální rizikové modely; Humans; Proportional Hazards Models; Race/ethnicity; karcinom z přechodných buněk; Chemotherapy; Aged; Ethnicity; senioři; lidé; Male; nádory močového měchýře; Retrospective Studies; Urothelial; Carcinoma, Transitional Cell; etnicita; retrospektivní studie; Age; SEER Program; Bladder; mužské pohlaví; Urinary Bladder Neoplasms; Sex